Lead like a woman - Deborah Smith Pegues (Eugene, Oregon Harvest House Publishers, 2020)
"Whether at work, at home, or in your community, you are already a leader. Deborah Smith Pegues challenges you to let go of unproductive thinking and empowers you to step boldly into the authority God has given you"-- Provided by publisher.
Includes bibliographical references.
Keywords: Leadership in women--Religious aspects--Christianity.